2017
DOI: 10.3389/fmicb.2017.01169
|View full text |Cite
|
Sign up to set email alerts
|

A Tiny RNA that Packs a Big Punch: The Critical Role of a Viral miR-155 Ortholog in Lymphomagenesis in Marek’s Disease

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that have been identified in animals, plants, and viruses. These small RNAs play important roles in post-transcriptional regulation of various cellular processes, including development, differentiation, and all aspects of cancer biology. Rapid-onset T-cell lymphoma of chickens, namely Marek’s disease (MD), induced by Gallid alphaherpesvirus 2 (GaHV2), could provide an ideal natural animal model for herpesvirus-related cancer research. GaHV2 encodes 26 mature miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…MDV-1 genome expresses a total of 26 mature miRNAs, encoded in 14 precursors as illustrated in Figure 1a, in three gene clusters named as the Meq-, mid-and LAT-clusters within the inverted repeat regions of the genome [8,11,17]. Several MDV-1 miRNAs, such as the viral miR-155 ortholog miR-M4-5p [18][19][20][21][22][23][24], miR-M3-5p [25], and miR-M7-5p [26], have been demonstrated to play key roles in MDV life cycle to regulate herpesvirus DNA cleavage/packaging, latency or especially virally-induced tumorigenesis. While it is known that most of the viral miRNA functions are related to the pathogenicity and/or oncogenicity [27,28], underlying molecular regulatory mechanisms mediated by these tiny RNAs in MDV biology still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MDV-1 genome expresses a total of 26 mature miRNAs, encoded in 14 precursors as illustrated in Figure 1a, in three gene clusters named as the Meq-, mid-and LAT-clusters within the inverted repeat regions of the genome [8,11,17]. Several MDV-1 miRNAs, such as the viral miR-155 ortholog miR-M4-5p [18][19][20][21][22][23][24], miR-M3-5p [25], and miR-M7-5p [26], have been demonstrated to play key roles in MDV life cycle to regulate herpesvirus DNA cleavage/packaging, latency or especially virally-induced tumorigenesis. While it is known that most of the viral miRNA functions are related to the pathogenicity and/or oncogenicity [27,28], underlying molecular regulatory mechanisms mediated by these tiny RNAs in MDV biology still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has largely focused on the role of those viral protein-coding genes. However, MDV also encodes a rich repertoire of non-coding RNAs (ncRNAs) including micro RNAs (miRNAs) and a viral telomerase RNA (vTR) [53][54][55][56][57][58][59][60]. vTR shares 88% sequence identity and the conserved stem-loop structure with its cellular homolog in the chicken (cTR) [54].…”
Section: Virulence Factors In the MDV Genomementioning
confidence: 99%
“…Recent studies have identified several host and viral miRNAs that potentially regulate MDVinduced tumorigenesis [14][15][16][17]. MiRNA-155 is a conserved multifunctional cellular miRNA that regulates the proliferation, migration and invasive growth of tumor cells, and is therefore closely associated with tumor initiation and progression [18][19][20][21], Studies show that the MD-encoded miR-M4-5p is the viral ortholog of cellular miR-155, and shares common targets with miR-155 and is involved in MD lymphomagenesis [16,17,22,23]. Zhao et al have implicated the critical role of MDV-miR-M4 in the induction of tumors, demonstrated the similarities function of both orthologs [24].…”
Section: Introductionmentioning
confidence: 99%